2003
DOI: 10.1785/0120020074
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Study on Scattering Characteristics of Shear Waves in Rock Samples

Abstract: To understand the scattering characteristics of seismic shear waves in the Earth, a laboratory physical model experiment in ultrasonic frequency range was performed. By analyzing waveform envelopes and particle motions of shear waves in media with different correlation distance and fluctuation intensity, we studied the strength of scattered wave excitation and the distortion of shear-wave polarization as a function of ka (wavenumber times the correlation distance). We used gabbro and granite as media having di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 41 publications
2
29
0
Order By: Relevance
“…Assigning the P-wave velocity of each mineral to appropriate locations on a surface photo image of a granite sample, Sivaji et al (2002) and Fukushima et al (2003) made 1-D velocity distributions. Granite is composed of feldspar, quartz, and biotite.…”
Section: Acf Of Velocity Inhomogeneity Revealed From Well-logs and Romentioning
confidence: 99%
“…Assigning the P-wave velocity of each mineral to appropriate locations on a surface photo image of a granite sample, Sivaji et al (2002) and Fukushima et al (2003) made 1-D velocity distributions. Granite is composed of feldspar, quartz, and biotite.…”
Section: Acf Of Velocity Inhomogeneity Revealed From Well-logs and Romentioning
confidence: 99%
“…The maps are then converted to P-velocity maps by assigning velocity values to the minerals (Fukushima 2000;Spetzler et al 2001). Microstructure images of the granitic rocks are obtained with 600-dpi (dot per inch) colour data.…”
Section: Random Medium Analysismentioning
confidence: 99%
“…The colour images are converted to tri-colour images to identify the three minerals: white, gray and black colour corresponding to plagioclase, quartz and biotite, respectively. However, the measurements of waveforms in different directions suggest that the effect of cracks on observed waveforms is not strong for frequencies less than 1 MHz (Nishizawa et al 1997;Fukushima 2000). The maps are then converted to P-velocity maps by assigning velocity values to the minerals (Fukushima 2000;Spetzler et al 2001).…”
Section: Random Medium Analysismentioning
confidence: 99%
“…To separate P and S waves, these authors performed measurements in two directions and then found projections of the displacement onto directions perpendicular and parallel to the surface. Fukushima et al (2003) used LDI to investigate polarisation of the shear waves in rock samples. The main advantage of using LDI in comparison with piezoelectric transducers is that the area of the measurement is much smaller than the wavelength, and that the full particle velocity vector can be recorded.…”
Section: Introductionmentioning
confidence: 99%